Application of multi-functional lactic acid bacteria strains in a pilot scale feta cheese production - Kamarinou, Christina S.; Papadopoulou, Olga S.; Doulgeraki, Agapi I.; Tassou, Chrysoula C.; Galanis, Alex; Chorianopoulos, Nikos G.; Argyri, Anthoula A. (Frontiers in Microbiology, 2023)
The aim of this study was to produce Feta cheese with enhanced quality and safety, and distinctive organoleptic characteristics by applying autochthonous lactic acid bacteria (LAB) with multi-functional properties as adjunct cultures. Feta cheeses were produced with the commercial lactococcal starter culture and the addition of 9 LAB strains (Lactococcus lactis SMX2 and SMX16, Levilactobacillus brevis SRX20, Lacticaseibacillus paracasei SRX10, Lactiplantibacillus plantarum FRX20 and FB1, Leuconostoc mesenteroides FMX3, FMX11, and FRX4, isolated from artisanal Greek cheeses) in different combinations to produce 13 cheese trials (12 Feta trials with the adjunct LAB isolates and the control trial). In addition, Feta cheese manufactured with FMX3 and SMX2 and control Feta cheese were artificially inoculated (4 log CFU/g) with Listeria monocytogenes (a cocktail of 4 acid or non-acid adapted strains). Cheese samples were monitored by microbiological and physicochemical analyses during ripening, and microbiological, physicochemical, molecular and sensory analyses during storage at 4 °C. The results showed that after manufacture, the LAB population was ca. 9.0 log CFU/g at all samples, whereas during storage, their population declined to 6.5-7.0 log CFU/g. In the Listeria inoculated samples, Listeria was absent after 60 days (end of ripening) and after 90 days in the adjunct culture, and in the control trials, respectively. Moreover, the addition of selected strains, especially Lcb. paracasei SRX10, led to cheeses with desirable and distinctive organoleptic characteristics. Furthermore, randomly amplified polymorphic PCR (RAPD‐PCR) molecular analysis confirmed that the multi-functional LAB strains were viable by the end of storage. Overall, the results of this study are promising for the use of autochthonous strains in various combinations with the commercial starter culture to satisfy industry requirements and consumer demands for traditional and high added value fermented products.